Jab tak hai jaan a Yash Chopra Romance - Chopra, Yash 1932-2012; Chopra, Aditya 1971-; Khan, Shah Rukh 1965-; Kaif, Katrina 1984-; Sharma, Anushka 1988- (Yash Raj, 2012)
Through a personal diary account a carefree media professional discovers that a Indian Army man who fascinates her has a love interest tucked away in London. Will she be able to bridge the gap and get close to him? Or will his past come back to haunt?